Effect of Permissive Dehydration on Induction and Decay of Heat Acclimation, and Temperate Exercise Performance - Neal, Rebecca A.; Massey, Heather C.; Tipton, Michael J.; Young, John S.; Corbett, Jo (Frontiers in Physiology, 2016)
Purpose: It has been suggested that dehydration is an independent stimulus for heat acclimation (HA), possibly through influencing fluid-regulation mechanisms and increasing plasma volume (PV) expansion. There is also some evidence that HA may be ergogenic in temperate conditions and that this may be linked to PV expansion. We investigated: (i) the influence of dehydration on the time-course of acquisition and decay of HA; (ii) whether dehydration augmented any ergogenic benefits in temperate conditions, particularly those related to PV expansion. Methods: Eight males [VO2max: 56.9(7.2) mL·kg−1·min−1] undertook two HA programmes (balanced cross-over design), once drinking to maintain euhydration (HAEu) and once with restricted fluid-intake (HADe). Days 1, 6, 11, and 18 were 60 min exercise-heat stress tests [HST (40°C; 50% RH)], days 2–5 and 7–10 were 90 min, isothermal-strain (Tre 38.5°C), exercise-heat sessions. Performance parameters [VO2max, lactate threshold, efficiency, peak power output (PPO)] were determined pre and post HA by graded exercise test (22°C; 55%RH). Results: During isothermal-strain sessions hypohydration was achieved in HADe and euhydration maintained in HAEu [average body mass loss −2.71(0.82)% vs. −0.56(0.73)%, P < 0.001], but aldosterone concentration, power output, and cardiovascular strain were unaffected by dehydration. HA was evident on day 6 reduced end-exercise Tre [−0.30(0.27)°C] and exercise heart rate [−12(15) beats.min−1], increased PV [+7.2(6.4)%] and sweat-loss [+0.25(0.22) L.h−1], P < 0.05 with some further adaptations on day 11 further reduced end-exercise Tre [−0.25(0.19)°C] and exercise heart rate [−3(9) beats.min−1], P < 0.05. These adaptations were not notably affected by dehydration and were generally maintained 7-days post HA. Performance parameters were unchanged, apart from increased PPO (+16(20) W, irrespective of condition). Conclusions: When thermal-strain is matched, permissive dehydration which induces a mild, transient, hypohydration does not affect the acquisition and decay of HA, or endurance performance parameters. Irrespective of hydration, trained individuals require >5 days to optimize HA.